Analisis Potensi Wilayah untuk Pengembangan Ternak Ruminansia di Kabupaten Lampung Tengah Area potential analysis is required as the right direction for development. Aim This study is to identify areas of the development of ruminant livestock in the Centr - I K Habsari; N Irwani (Politeknik Negeri Lampung, 2021)
Area potential analysis is required as the right direction for development. This study aims to identify areas of the development of ruminant livestock in the Central Lampung Regency. The method used is the analysis of livestock density and Location quotient. Data that used is secondary data from Central Lampung In Lift Year 2020—2021. The method used is descriptive-analytical. The result showed that Selagai Lingga sub-district is the most priority location for the development of ruminants, second priority were Sendang Agung and Trimurjo sub-districts, and the third priority were Anak Tuha and Bumi Ratu Nuhan. Based on the Location Quotient (LQ) analysis, Selagai Lingga Sub-District is categorized as a basic sector for goats and sheep, Sendang Agung for Buffalo and sheep, Anak Tuha and Bumi Ratu Nuban are the basic sector for buffalo, goat, and sheep. Seputih Agung is the basic sector for Cattle.